1997
DOI: 10.1111/j.1399-3054.1997.tb04792.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of pathogen resistance and pathogenesis‐related genes in tobacco by a heat‐stable Trichoderma mycelial extract and plant signal messengers

Abstract: Heat‐stable mycelial extracts of the nonpathogenic fungus Trichoderma longibrachiatum induced resistance in tobacco seedlings (Nicotiana tabacum L. cv. Wisconsin 38) to the pathogen Phytophthora parasitica var. nicotianae (race 0), which did not involve a hypersensitive response. Resistance could not be induced with mycelial extract prepared in the same manner from P. parasitica. The nonpathogenic mycelial extract induced expression of PR‐1b and osmotin (PR‐5) genes to a higher level than did mycelial extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Cev1 mutant plants also have short roots with an excess of root hairs and increased anthocyanin accumulation in petioles (Ellis and Turner, 2001), whereas crp5 plants present an altered trichome development and an early senescence phenotype (Bowling et al ., 1997; Yoshida et al ., 2002). This complexity is further evidenced by the observation that altering the levels of host signal molecules may mimic but not exactly duplicate pathogen‐induced symptoms (Bent et al ., 1992; Chang et al ., 1997). The dependence of interactions of pathogen with host signaling on the host genetic status is emphasized by the distinct difference in flowering response by Columbia and C‐24 whereby V. dahliae accelerates flowering in Columbia and delays flowering in C‐24 (Figure 1c).…”
Section: Discussionmentioning
confidence: 99%
“…Cev1 mutant plants also have short roots with an excess of root hairs and increased anthocyanin accumulation in petioles (Ellis and Turner, 2001), whereas crp5 plants present an altered trichome development and an early senescence phenotype (Bowling et al ., 1997; Yoshida et al ., 2002). This complexity is further evidenced by the observation that altering the levels of host signal molecules may mimic but not exactly duplicate pathogen‐induced symptoms (Bent et al ., 1992; Chang et al ., 1997). The dependence of interactions of pathogen with host signaling on the host genetic status is emphasized by the distinct difference in flowering response by Columbia and C‐24 whereby V. dahliae accelerates flowering in Columbia and delays flowering in C‐24 (Figure 1c).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence of plant ISR by Trichoderma was first described by (Calderon et al, 1993) through induction of hypersensitive response (HR) and phytoalexin synthesis by T. viride cellulase in grapevine cell cultures. Later, Chang et al (1997) demonstrated the capability of heat-stable mycelial extracts of T. longibrachiatum to induce disease resistance against Phytophthora parasitica by induction of higher level of PR-1b and PR-5 in tobacco, Nicotiana tabacum (Chang et al, 1997). In addition, reports on soil inoculation with T. harzianumT39 imparted resistance to leaves of bean plants, that is, parts spatially separated from the site of inoculation against B. cinerea and C. lindemuthianum have also been documented (Bigirimana et al, 1997;De Meyer et al, 1998).…”
Section: Induced Resistancementioning
confidence: 98%
“…Thus, cellulose from Trichoderma viride was found to induce plant defence responses in grapevine cell cultures (Calderón et al, 1993), while control of Phytophthora parasitica var. nicotianae on tobacco by T. longibrachiatum was linked to the induction of plant defences (Chang et al, 1997). Subsequent work on control of B. cinerea on a number of plant species using the BCA T. harzianum T39 provided further evidence for the involvement of induced plant defences (De Meyer et al, 1998).…”
Section: Induction Of Resistance By Biological Control Agentsmentioning
confidence: 99%